2011
DOI: 10.3109/0142159x.2011.599893
|View full text |Cite
|
Sign up to set email alerts
|

Does medical student willingness to practise peer physical examination translate into action?

Abstract: Background: Peer physical examination (PPE) is commonly used in clinical skills teaching to allow students to practice physical examination techniques on each other. Previous studies have demonstrated medical students' generally positive attitudes towards PPE, but the correlation between student attitude and actual practice of PPE has yet to be examined. Aim: To determine if a positive student attitude towards PPE leads to subsequent action. Methods: The target population were MBBS I students (2006-2007 cohort… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
31
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(40 citation statements)
references
References 16 publications
9
31
0
Order By: Relevance
“…The EFS questionnaire asks students to indicate which areas of the body they would not be willing to examine on a peer or have examined by a peer. Numerous authors have reported that students are more willing to examine, rather than be examined by, a peer [ 11 , 33 , 34 ], and this appeared to be consistent with the present study. Students entering an osteopathy program are likely to be aware that their course will include a substantial amount of time devoted to learning clinical assessments and manual therapy skills [ 3 ].…”
Section: Discussionsupporting
confidence: 92%
“…The EFS questionnaire asks students to indicate which areas of the body they would not be willing to examine on a peer or have examined by a peer. Numerous authors have reported that students are more willing to examine, rather than be examined by, a peer [ 11 , 33 , 34 ], and this appeared to be consistent with the present study. Students entering an osteopathy program are likely to be aware that their course will include a substantial amount of time devoted to learning clinical assessments and manual therapy skills [ 3 ].…”
Section: Discussionsupporting
confidence: 92%
“…Female medical students showed a higher level of concern regarding PPE than did men; this finding is similar to previously reported results [13-16]. This gender difference did not reach statistical significance between the two classes of osteopathic students, even if the female students in the full-time osteopathic curriculum (who were younger than their counterparts in the part-time curriculum and as old as the medical students) tended to show a slightly weaker acceptance of PPE than did the men.…”
Section: Discussionsupporting
confidence: 92%
“…Evidence has been collected on the influence of gender on the acceptability of PPE [9,12-16]. Usually women are more reluctant to engage in PPE, especially with students of the opposite gender.…”
Section: Introductionmentioning
confidence: 99%
“…1,2 Although PPE has been integrated into formal teaching activities, Chen and colleagues showed that 80 per cent of students perform PPE outside of the classroom setting. 3 Benefi ts of PPE include the opportunity for students to experience a physical examination from a patient ' s perspective, learn a 'normal' examination, practise in a low-risk environment and receive feedback. 4,5 Although direct observation and feedback is an important component of learning physical examination skills, it occurs infrequently.…”
Section: Students Oftenmentioning
confidence: 99%
“…Previous studies have shown a high degree of willingness by students to perform PPE of non‐sensitive areas, although there are some differences by gender, and religious and cultural backgrounds . Although PPE has been integrated into formal teaching activities, Chen and colleagues showed that 80 per cent of students perform PPE outside of the classroom setting . Benefits of PPE include the opportunity for students to experience a physical examination from a patient's perspective, learn a ‘normal’ examination, practise in a low‐risk environment and receive feedback …”
Section: Introductionmentioning
confidence: 99%